The Role of Career Guidance in Preparing Vocational School Students in the Building Construction Department for the Workforce - Zulaikhah, Siti; Sutopo, Yeri; Kusumawardani, Rini; Supraptono, Eko; Fuad, Muhammad Nur; Nurfitriyani, Sintya Andryati (Universitas Negeri Semarang, 2024)
The Central Bureau of Statistics indicates that the open unemployment rate for vocational high school graduates remains one of the highest categories at 9.60%. In vocational education, particularly in the Design Modeling and Building Information program, this gap is also evident in the low preparedness of students in understanding the career paths available and the lack of strategies they have to enter the workforce. This study aims to analyze the role of career guidance in preparing vocational high school students for the workforce. The role of career guidance is focused on three main directions for vocational high school graduates: working in industry, continuing education to higher education, and entrepreneurship. This study uses a quantitative approach with a sample of 72 students from Vocational High School Negeri 3 Semarang, divided into two classes. The sampling technique used is total sampling. Data collection was conducted through work readiness and career guidance questionnaires, as well as interviews with instruments that were previously validated by experts. Data analysis included tests for normality, homogeneity, linearity, and simple linear regression. The results showed that career guidance plays a very significant role in the work readiness of students with a value of 68.8%. Meanwhile, the remaining 31.2% is influenced by other factors not explored in the study, such as motivation, interests, talents, and effort. This was supported by interview results, where students stated that career guidance helped them recognize their potential, explore job opportunities, and begin planning their next steps, whether for employment, continuing education, or entrepreneurship.